2012
DOI: 10.1002/pd.3892
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequencing of maternal plasma to identify Down syndrome and other trisomies in multiple gestations

Abstract: Objective Studies on prenatal testing for Down syndrome (trisomy 21), trisomy 18, and trisomy 13 by massively parallel shotgun sequencing (MPSS) of circulating cell free DNA have been, for the most part, limited to singleton pregnancies. If MPSS testing is offered clinically, it is important to know if these trisomies will also be identified in multiple pregnancies.Method Among a cohort of 4664 high-risk pregnancies, maternal plasma samples were tested from 25 twin pregnancies (17 euploid, five discordant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(170 citation statements)
references
References 13 publications
2
161
1
Order By: Relevance
“…Although the total fetal fraction of twin pregnancies might be higher than that of singletons10, the individual contribution from each twin is generally lower than that of a singleton8, 9; however, there may be exceptions. In our study, the average combined fetal fraction of both twins (16.1%) was higher than determined previously for singletons over similar gestational‐age ranges (12.6%; P  = 0.001)21, and higher still than the average fetal fraction for a single twin (7.8%; P  < 0.0001), consistent with the previously mentioned studies.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although the total fetal fraction of twin pregnancies might be higher than that of singletons10, the individual contribution from each twin is generally lower than that of a singleton8, 9; however, there may be exceptions. In our study, the average combined fetal fraction of both twins (16.1%) was higher than determined previously for singletons over similar gestational‐age ranges (12.6%; P  = 0.001)21, and higher still than the average fetal fraction for a single twin (7.8%; P  < 0.0001), consistent with the previously mentioned studies.…”
Section: Discussionmentioning
confidence: 94%
“…Traditionally, prenatal aneuploidy screening options have been less robust for twin pregnancies than for singletons6, whereas the miscarriage risk associated with invasive diagnostic procedures is higher in twins7. Preliminary data have suggested that NIPT is a feasible test option for twin gestations8, 9, 10. Currently, due to the paucity of reported studies in twins, professional societies and others have called for more studies on NIPT performance in twin gestations11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple gestation pregnancies have been reported to have higher fetal fractions. 12,14 Therefore, group comparisons of ccf DNA levels and fetal fractions were conducted after excluding data from the 16 sets of twins. The twin results were, however, included in the analyses of demographic information and z-scores.…”
Section: Resultsmentioning
confidence: 99%
“…The MaterniT21 PLUS test sensitivity ranges from 99.1% for trisomy 21, > 99.9% for trisomy 18, and 91.7% for trisomy 13, while maintaining a very low falsepositive rate. Data from the validation studies are showed in Table 2 [7,28,42,58]. The analytical performance of selective microdeletions/duplications and trisomy 16/22, was > 99% regarding specificity, while sensitivity was 60-86% for 3-6 Mb deletions, 85-90% for 7-11 Mb deletions and > 99% for trisomy 16/22 [30,58].…”
Section: Maternit21 Plus (Sequenom Laboratories)mentioning
confidence: 99%